Kedudukan Saksi Mahkota (Kroongetuige) Dalam Pembuktian Tindak Pidana Pembunuhan Di Persidangan - Saputro, Eko Condro, Hartanto, S.H., M.Hum, Marisa kurnianingsih, SH. M.Kn (2015)
Crown witness is another equally defendant committed the crime splitsing held under Article 142 Criminal Procedure Code); Supreme Court Decision No. 66K / Cr / 1967 dated October 25, 1967, and the Supreme Court Decision No. 1986 K / Pid / 1989 dated March 21, 1990; Witness and Victim Protection Agency (hereinafter Agency) (1) Protection against the crown witness of aspects of human rights has the right to not incriminate himself from the investigation to the trial in the court process, in accordance with Article 50 and Article 68, section 244, 263, 213 Criminal Procedure Code and Article 17 of Law No. 39 Year 1999 on human rights; (2) The position of the crown witness in the process of proving the crime of murder in the trial court (a) are based on certain conditions, namely in the form of inclusion and against criminal actions examined by the separation mechanism (splitsing) as stipulated in Article 142 Criminal Procedure Code. (b) In accordance with Article 10 paragraph (2) Witness Protection Act, the crown witness is entitled to legal incentives in the form of leniency. that his testimony could be considered a judge in a criminal ease to be dropped. (3) Constraints use crown witness in a murder case evidence at trial: (a) Constraints on a defendant who is not willing to be a crown witness, for fear his deeds will be revealed at the trial. (b) Constraints on the Public Prosecutor for the separation Determining docket (splitsing) stipulated in Article 142, Criminal Procedure Code and Supreme Court Decision No. 1986 K / Pid / 1989 dated March 21, 1990 and the Public Prosecutor difficulty in getting witnesses crown (c) Constraints on the Court of Justice (1) The use of crown witness difficult or affect / less fairnya Judge's decision. (2) Statement of witness lies the crown could contain measures that aim to save another defendant then be threatened in violation. Keywords: Crown Witness (kroongetuige); Crime Murder, Position at trial.